PENGGUNAAN GAYA BAHASA PERSAMAAN DALAM INJIL LUKAS - Novillanti, Jeanly (Educatio Vitae, 2014)
This research tries to reveal the use of simile in Luke. It aims to describe(1) formal forms of simile, (2) lingual forms of tenor and vehicle, (3) tenor andvehicle relations, and (4) the meaning of similarities.The research is qualitative-descriptive in nature. The data of the researchare sentences and paragraphs existing in Luke (Indonesian Bible Society, 2005).The number of the data is 70 quatations.The result of the data analysis shows (1) formal forms area: (a) explicitlyexpressed using the words seperti, sama seperti, demikian juga, seumpama, samadengan, demikian jadinya, demikian pulalah, sebesar, seindah, senasib dan (b)implicitly expressed, (2) lingual forms of tenor and vehicle fillers are (a)word+ss+word, (b) word+ss+phrase, (c) word+ss+clause, (d) phrase+ss+phrase,(e) phrase+ss+clause, (f) clause+ss+word, (g) clause+ss+phrase, (h)clause+ss+clause, (3) Tenor and vehicle relation consist of concrete-abstract,abstract-concrete, concrete-concrete, abstract-abstract, and (4) The meaning ofsimilarities is grouped into two, namaly closed similarities (42 data) and opensimilarities (28 data).